Effect of CO₂ laser-induced crystallization on ErF₃-doped tellurite-germanate oxy-fluoride glass - Leśniak, Magdalena; Zając, Patryk; Talik, Wojciech; Ziąbka, Magdalena; Kochanowicz, Marcin; Miluski, Piotr; Zawadzki, Witold; Dzierżęga, Krzysztof; Dorosz, Dominik; Jeleń, Piotr (Photonics Letters of Poland, 2025)
Glass-ceramic materials, obtained through controlled crystallization of glasses, combine the advantageous properties of both glasses and crystals, making them useful for optical applications. Conventional thermal treatment technique is widely used to induce crystallization in glass. Laser-induced crystallization (LIC) provides a localized and controlled method to modify the glass structure and tailoring its optical properties. This study investigates the structural and luminescent properties of Er³⁺-doped tellurite-germanate glass-ceramic obtained through CO₂ laser irradiation of the parent glass. The observed structural changes induced by laser irradiation led to the crystallization of BaF₂, enhancing the luminescent properties of the material. Full Text: PDF References D.F. Franco, F.J. Caixeta, L.V. Albino, T.A. Lodi, J.R. Orives, E.O. Ghezzi, M. Nalin, "Terbium-doped transparent glass-ceramics containing TbPO4 crystals: A promising material for photonic applications", Opt. Mater.: X. 20, 100272 (2023). CrossRef Y. Wu, C. Niu, L. Wang, M. Yang and S. Zhang, "Structural, luminescence, and temperature sensing properties of the Er3+-doped germanate-tellurite glass by excitation at different wavelengths", J. Lumin. 266, 120323 (2024). CrossRef E.E. Brown, Z.D. Fleischman, J. McKay and M. Dubinskii, "Spectroscopic characterization of low-phonon Er-doped BaF2 single crystal for mid-IR lasers", Opt. Mater. Express 11, 575-584 (2021). CrossRef F.J. Deubener, M. Allix, M.J. Davis, A. Duran, T. Höche, T. Honma, T. Komatsu, S. Krüger, I. Mitra, R. Müller, S. Nakane, M.J. Pascual, J.W.P. Schmelzer, E.D. Zanotto, S. Zhou, "Updated definition of glass-ceramics", J. Non-Cryst Solids. 501, 3-10 (2018). CrossRef R. Que, M. Lancry, M. Cavillon and B. Poumellec, "How to Crystallize Glass with a Femtosecond Laser", Crystals. 14, 606 (2024). CrossRef F. Mona, N.S. Yazd, A. Keshavarzi and A. Doosti, "Anisotropic crystallization of YAG on the surface of glass by CO2 laser irradiation", Cryst. Eng. Comm. 24, 2753 (2022). CrossRef J. Chacaliaza-Ricaldi, V.A.G. Rivera, I.C. Pinto, Y. Messaddeq and E. Marega, "Germanate-tellurite glasses with low Er3+ ions concentration and their radiative emissions", J. Non-Cryst. Solids. 638, 123063 (2024). CrossRef Y. Ren, J. Dong, W.Wang, J. Li, X. Cao, Q. Song, M. Wu, X. Qian, Y. Xue, Q. Wang, H. Tang, X. Xu and J. Xu, "Crystal growth and spectroscopic analysis of Ho,Pr:BaF2 crystal for 3 μm mid-infrared emission", J. Lumin. 275, 120743 (2024). CrossRef S. Ibrahim, A.A. El-Kheshen, M. Abdel-baki, A.M. Fayad, Y.M. Hamdy, Mohamed M. Ibrahim and M.A. Marzouk, "Synthesis and characterization of erbium silica glass and glass-ceramics for potential low-emissivity coating applications", Ceram. Internal. 51, 458 (2025). CrossRef A. Bitam, S. Khiari, M. Diaf, H. Boubekri, E. Boulma, C. Bensalem, L. Guerbous and J.P. Jouart, "Spectroscopic investigation of Er3+ doped BaF2 single crystal", Opt. Mater. 82, 104 (2018). CrossRef G. Guery, A. Fargues, T. Cardinal, M. Dussauze, F. Adamietz, V. Rodriguez, J. D. Musgraves, K. Richardson, P. Thomas, "Impact of tellurite-based glass structure on Raman gain", Chem. Phys. Lett. 554, 123 (2012). CrossRef H.O. Tekin, L.R.P. Kassab, S.A.M. Issa, C.D.S. Bordon, M.S. Al-Buriahi, F.O.P. Delboni, G. Kilic, E.S. Magalhaes, "Structural and physical characterization study on synthesized tellurite (TeO2) and germanate (GeO2) glass shields using XRD, Raman spectroscopy, FLUKA and PHITS", Opt. Mater. 110, 110533 (2020). CrossRef H. Kumari, K. Patel, S.K. Dhiman, S.K. Mahajan, G.F. Ansari, "Studies of structural and optical properties of tungsten tellurite glasses", Mater. Today: Proc. 59, 1127-1131 (2022). CrossRef J.L. Clabel H., J.V.P. Valverde, G. Lozano C.E. Marega Jr., V.R. Mastelaro, C.R. Mendonça, "Nonlinear optical properties of La3+-Doped tellurite-zinc glasses: Impact of chemical bonding and physical properties via Raman and XPS", Ceram. Int. 51, 844-855 (2025). CrossRef O.N. Koroleva, M.V. Shtenberg, R.T. Zainullina, S.M. Lebedeva, L.A. Nevolina, "Vibrational spectroscopy and density of K2O–B2O3–GeO2 glasses with variable B/Ge ratio", Phys. Chem. Chem. Phys. 21, 12676-12684 (2019). CrossRef